DETERMINING OF THE MODULUS OF ELASTICITY BY MEASUREMENT OF THE RELATIVE STRAINS WITH STRAIN GAGES - LABASOVA, Eva; LABAS, Vladimir (Trends in education, 2016)
The contribution is focused on estimating the Young modulus of the testing sample of rectangular cross-section by static method. The sample (bar) was loaded by simple bending. Theoretical basis for determining the modulus of elasticity are determined by linear elasticity and strength theory and they define the relation between Young modulus, maximum normal stress at the edge fibers of the crosssection and the relative strains. Relative strains are determined by using measurement apparatus and measurement system Quantum X MX 840. The aim of the work is to increase intellectual and practical skills of students in second and third level of technical universities.
Keywords: Young modulus; simple bending; stress in the cross-section; relative strain.